The Effect of Sea Shells Powder on the Growth and Yield of Mungbean at Peat Soil - Sinaga, Siska Rauni; Zulfita, Dwi; ., Surachman (Jurnal Sains Pertanian Equator, 2019)
Mung bean (Vigna radiata L.) is leguminoceae plant with high protein and big potential to be cultivated. Application of sea shells powder have an important role in improving the chemistry nutrition of the peat soil. The aim of the study is to determine the best dose of sea shells powder on the growth and yield of mungbean plants in peat soil. This research was carried out on experimental field Agriculture Faculty of Tanjungpura University, Pontianak which took place from April to June 2019. The method used was Completely Randomized Design (CRD) consisted of 5 treatment levels, 5 replications, and 4 sample plants. Application of the sea shells powder treatment consist of k1 = 5 ton/ha, k2 = 10 ton/ha, k3 = 15 ton/ha, k4 = 20 ton/ha, and k5 = 25 ton/ha. The observed variables in this research consisted of plant height (cm), root volume (cm3), plant dry weight (g), number of pods (pods), dry seed weight (g), dry seed weight 100 (g). The results showed that the best dose of sea shells powder growth and yield of mung bean was a dose of 5 ton/ha or equivalent to 62 g/polybag.Keywords : mungbean, peat soil, sea shells powder.